(untitled) (The Review of Diabetic Studies, 2025)
Background: This study examines nurses’ MRSA knowledge, attitudes, and protocol compliance. Settings and Design: a cross-sectional study was conducted from April to May 2023, 220 healthcare nurses in Al Madinah Al Munawara, Saudi Arabia, completed a cross-sectional questionnaire. Methods and Material: A questionnaire developed from nurse knowledge surveys assessed knowledge. A Likert scale assessed attitude. The compliance part asked respondents whether they followed MRSA patient care guidelines. Google Forms sent the poll to 300 nurses through social media and apps. Results: The majority of respondents (67.7%) scored Poor knowledge indicating a low level of knowledge about MRSA. Most nurses have a positive attitude and good self-compliance to MRSA preventive measures. There is a significant relationship between nurses’ knowledge levels and their attitudes (p=0.001). However, no significant relationship was found between nurses’ knowledge levels and their self-compliance. Conclusions: Nurses’ knowledge and attitudes exhibit notable variations contingent upon their tenure as registered nurses, their present occupational environment, and their educational attainment. Furthermore, a lack of substantial correlation exists between the self-compliance of nurses and any of the demographic variables. The aforementioned findings offer significant insights into the variables that may impact the knowledge levels of nurses, thereby presenting potential utility in the formulation of strategies aimed at enhancing knowledge among nursing personnel. Future Recommendation: Nurses must understand MRSA to improve patient outcomes and prevent its spread. Nurses should prioritize MRSA prevention and treatment training to properly tackle this difficult illness.